Milk, its nature, composition and yield - Bolton, Lilia Grace (My University, 1900)
Introduction: Milk is a fluid opaque in color and composed of water and certain solid constituents, part in solution and part in suspension. There is 11.5 percent of total solids found in milk 8.5 percent of these are solids, not fat, while the remaining 3 percent are fat. Chas. Cameron, the public analyst never found the total solids in mixed milk to fall below 12%. There are many variations due to a number of different causes. Among them may be individuality, breed of cow, period of lactation and the feeding. In choosing milk cows, choose a good milking breed. Many give large quantities, but do not give rich milk. It may be also that the cow gives a large yield of milk and it may be of good quality. The Guernsey give a heavy flow of milk which is highly colored and shows a large percent of butter fat. It is undisputed today among the dairymen that the Guernsey butter has the highest natural color of any breed and that they are the most economical butter producers.
Citation: Bolton, Lilia Grace. Milk, its nature, composition and yield. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Dairy Cows; Guernsey Cows; Milk; Butter; Animal Husbandry; Theses; Manuscripts (documents)